Improvement of the Stability of Quantum-Dot Light Emitting Diodes Using Inorganic HfOx Hole Transport Layer - Yun, Jung Min; Park, Min Ho; Kim, Yu Bin; Choi, Min Jung; Kim, Seunghwan; Yi, Yeonjin; Park, Soohyung; Kang, Seong Jun (MDPI Open Access Publishing, 2024)
One of the major challenges in QLED research is improving the stability of the devices. In this study, we fabricated all inorganic quantum-dot light emitting diodes (QLEDs) using hafnium oxide (HfOx) as the hole transport layer (HTL), a material commonly used for insulator. Oxygen vacancies in HfOx create defect states below the Fermi level, providing a pathway for hole injection. The concentration of these oxygen vacancies can be controlled by the annealing temperature. We optimized the all-inorganic QLEDs with HfOx as the HTL by changing the annealing temperature. The optimized QLEDs with HfOx as the HTL showed a maximum luminance and current efficiency of 66,258 cd/m2 and 9.7 cd/A, respectively. The fabricated all-inorganic QLEDs exhibited remarkable stability, particularly when compared to devices using organic materials for the HTL. Under extended storage in ambient conditions, the all-inorganic device demonstrated a significantly enhanced operating lifetime (T50) of 5.5 h, which is 11 times longer than that of QLEDs using an organic HTL. These results indicate that the all-inorganic QLEDs structure, with ITO/MoO3/HfOx/QDs/ZnMgO/Al, exhibits superior stability compared to organic-inorganic hybrid QLEDs.